Radial gradients in PET monofilaments: A Raman mapping and SAXS tomography study. (3rd January 2022) - Perret, E.; Chen, K.; Braun, O.; Muff, R.; Hufenus, R.
Abstract: Surface properties of monofilaments can be tailored with radial structural gradients, which is of specific interest for technical textile applications. Radial gradients in fine (≤ 40 μm thick) poly(ethylene terephthalate) monofilaments have been studied with high-resolution Raman mapping and one-dimensional microbeam small-angle x-ray scattering tomography. Filaments have been melt-spun by using online and offline drawing techniques. Radial structural gradients are strongly affected by the drawing method. Raman mapping revealed that offline drawn filaments have a higher crystallinity in the core than in the surface region, whereas the opposite is the case for online drawn filaments. The molecular alignment was the highest in the core for all filaments. Microbeam SAXS tomography revealed that the long-spacing between crystals, in the direction of the fiber axis, increases towards the fiber surface. Fibers that have been drawn to a larger extent, resulting in improved tensile strength, have been found to have a larger long-spacing. Graphical abstract: Image 1 Highlights: 2D Raman maps of thin PET fiber cross-sections (diameter ≤40 μm). Radial gradients in crystallinity and molecular alignment from Raman maps. 1D SAXS tomography for analyzing radial gradients in long-spacing and crystal tilts. The average long-spacing increases with draw ratio.